Neutrophil count predicts poor outcome despite recanalization after endovascular therapy. (30th July 2019) - Boisseau, William; Desilles, Jean-Philippe; Fahed, Robert; Kyheng, Maeva; Zuber, Kevin; Sabben, Candice; Taylor, Guillaume; Ben Maacha, Malek; Maier, Benjamin; Botta, Daniele; Escalard, Simon; Ciccio, Gabriele; et al.
Abstract : Objective: To identify early prognostic factors of poor clinical outcome in patients treated by endovascular therapy (EVT) with successful recanalization. Methods: We reviewed our monocentric prospectively collected EVT database of patients with anterior circulation acute ischemic stroke (AIS) from January 2016 to April 2018 who had achieved successful recanalization (Thrombolysis in Cerebral Infarction score ≥ 2b) at the end of the procedure. A poor outcome was defined as a 3-month modified Rankin Scale score of ≥3. Results: A total of 324 patients were included, among whom 186 (57.4%) had a poor outcome. Multivariate logistic regression indicated that age (per 10-year increase, odds ratio [OR] 1.34, 95% confidence interval [CI] 1.12–1.60), baseline NIH Stroke Scale score (per 1-unit increase, OR 1.09, 95% CI 1.04–1.15), initial infarct volume (per a log+1 increase, OR 1.34, 95% CI 1.05–1.67), blood glucose level (per a log+1 increase, OR 2.60, 95% CI 1.01–6.66), and neutrophil count (per 1, 000-unit increase, OR 1.08, 95% CI 1.01–1.17) were all associated with poor clinical outcome. Conclusions: In addition to baseline severe AIS criteria, high neutrophil count and high blood glucose, known from experimental studies to be associated with downstream microvascular thromboinflammation, are independently associated with poor outcome. These findings support a deleterious role of thromboinflammation in patient recovery despite successful recanalization.